Improving API Usability. - MYERS, BRAD A.; STYLOS, JEFFREY (Communications of the ACM, 2016)
The article presents suggestions for improving the usability standards of application programming interfaces (APIs). The multivariate aspects of API security and evaluation are examined, the alleged impacts of poor usability design of APIs on computer programmers are discussed, and information is offered on the impact of agile software development on APIs.